2023
DOI: 10.25307/jssr.1246992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rapid Body Weight Loss on Balance and Functional Mobility in Obese Individuals after Laparoscopic Adjustable Gastric Banding Operation

Abstract: The purpose of this study was to evaluate the effect of rapid weight loss on static balance and functional mobility among excessively obese patients undergoing Laparoscopic Adjustable Gastric Banding (LAGB) surgery. Subjects (8 females; BMI >35 kg/m2) underwent baseline measurements before LAGB surgery, followed by subsequent evaluations at 6 weeks, 12 weeks, and 24 weeks during the follow-up appointments. During each evaluation, various assessments were conducted, including measurements of anthropome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Similarly, in our study, unlike GA measurements, a significant reduction in perimeter was observed postoperatively in the CG group. Kucuk Yetgin et al’s [ 10 ] study revealed that while there was no significant difference in eyes-closed static balance during the rapid weight loss period before and after Laparoscopic Adjustable Gastric Banding Surgery at 6, 12, and 24 weeks, a statistically significant improvement in eyes-open static balance occurred at 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in our study, unlike GA measurements, a significant reduction in perimeter was observed postoperatively in the CG group. Kucuk Yetgin et al’s [ 10 ] study revealed that while there was no significant difference in eyes-closed static balance during the rapid weight loss period before and after Laparoscopic Adjustable Gastric Banding Surgery at 6, 12, and 24 weeks, a statistically significant improvement in eyes-open static balance occurred at 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been concluded that in women with overweight or obesity [ 6 8 ], there is an increased sway velocity in both eyes-open and eyes-closed conditions, indicating the adverse impact of obesity on postural stability. To the best of our knowledge, there is a limited body of research investigating static balance both in the preoperative period of bariatric surgery [ 9 ] and during the period of rapid weight loss following bariatric surgery [ 10 ]. However, there is currently no study available that examines the impact of corrective exercises on static balance in bariatric surgery participants after the surgery.…”
Section: Introductionmentioning
confidence: 99%